Dissenting Gods. Forms of Queer Religiosity in writing, visual art and performance in Latin America - Cabezas Baamonde, Laura (Universidad Pedagógica y Tecnológica de Colombia, 2022)
The purpose of this article is to analyze the intersection between religiosities and dissident sexualities in four contemporary aesthetic experiences in Latin America. We are interested in exposing how religious discourse can function as a mode of aesthetic experimentation that strikingly questions and subverts the established order. With this purpose, we work in the frame of literacy criticism and visual arts with the following materials: the Colombian artist Carlos Motta's art exhibition in Buenos Aires and the incorporation of Marcella Althus-Reid's indecent theology, Alejandro Tantanian's artwork, the essay writing of the Brazilian Tatiana Nascimento and the Transvestite Museum of Peru by Giuseppe Campuzano (in his role as researcher and performer). We consider that these works stage a queer religiosity that, from writing, visual arts and performance, designs new transfeminist and decolonial protocols of reading, subverting the Western, Catholic, colonial and modern legacy.